Enhancing student satisfaction and academic performance through school courtyard design: a quantitative analysis - Salameh, Muna; Touqan, Basim; Suliman, Abubakr (Architectural engineering and design management, 2024)
Traditionally, students' overall satisfaction with their educational experience was typically measured using a single question or a straightforward 'yes' or 'no' response. However, this approach might not capture their complete assessment of other aspects of satisfaction. The design of School Courtyard is expected to be one of these aspects, and it will be the subject of this quantitative research. To gather the data, a self-administered survey was made available to a sample of secondary school students from two private schools. To investigate and validate the connection between School Courtyard Design, Courtyard Suitability and Courtyard Attractiveness with Students' Satisfaction, three hypotheses were developed. To evaluate the viability of the developed hypotheses, software namely SPSS (Statistical Package for Science Software) was used to carry out several tests, including regression analysis and correlation coefficient. The results showed a high relationship significance between the School Courtyard Design and Students' Satisfaction with a chance of 37.5%. Student satisfaction can be predicted also by Courtyard Suitability with a 22.9% chance. Finally, Students' Satisfaction can be additionally predicted by the Courtyard Attractiveness with a 24.7% chance. The research reveals the courtyard design needs, enhancing student satisfaction and academic performance, benefiting architects, experts, and practitioners.